Eocene-Oligocene syn-rift deposition in the northern Gulf of Tonkin, Vietnam. (January 2020) - Fyhn, Michael B.W.; Hoang, Bui H.; Anh, Nguyen T.; Hovikoski, Jussi; Cuong, Tong D.; Dung, Bui V.; Olivarius, Mette; Tuan, Nguyen Q.; Toan, Do M.; Tung, Nguyen T.; Huyen, Nguyen T.; Cuong, Trinh X.; et al.
Abstract: Reconstruction of non-marine syn-rift deposition in ancient basins is challenged by intense deformation, rapid lateral facies variation and limited biostratigraphic resolution. This affects petroleum resource assessments that relies on prediction of basin fill. The northern Gulf of Tonkin contains such non-marine-dominated rift system. The area is in an early stage of exploration. Depositional facies analysis based on all existing 2D seismic and well data suggests that Eocene-Oligocene deposition in grabens and half-grabens occurred in three steps. This resulted in formation of three successive packages, namely the rift initiation-, the rift development- and the rift termination succession. Rift initiation deposits are mainly composed by alluvial-fluvial strata deposited in segmented and often isolated grabens and half-grabens. As rifting progressed, faults joined and rift depressions merged into larger, coherent areas of deposition. Faulting peaked, which resulted in rapid creation of accommodation space, relief, and the development of deep lakes, alluvial fans and fan deltas. Elsewhere, floodplain, deltaic and shallow lake deposits comprise most of the rift development succession. As rift-subsidence declined, floodplain, deltaic and shallow lake deposits filled accommodation space and therefore dominate the rift termination succession. Structuring by strike-slip faulting and inversion complicates sequence stratigraphic analysis. Moreover, diachronic rift culmination caused the rift initiation, -development and -termination successions to vary laterally in age, further obscuring sequence stratigraphic analysis. Even so, tectonostratigraphic grouping into these three units allows a meaningful mapping of gross-depositional facies. The locally developed deep lake successions, potentially containing petroleum source rocks and seals, together with areas including potential deltaic, fan-delta, fluvial and turbidite reservoir sand suggest play types similar to those working in the Chinese part of the Beibuwan Basin. The most prospective areas are least explored suggesting an overlooked petroleum potential in the northern Gulf of Tonkin. Highlights: Eocene–Oligocene syn-rift strata in northern Gulf of Tonkin is mainly continental. Structuration, lateral variation and data limitations challenge syn-rift analysis. The syn-rift includes rift initiation, rift development and rift termination units. Subdivision into these three units enables depicting deposition through time. Rift development deposits include lacustrine source rocks and sandstone reservoirs.